Surface tension profiles of nanofluid containing surfactant during microwave irradiation - Tanaka, K.; Asakuma, Y.; Saptoro, Agus; Phan, Chi (2017)
© Published under licence by IOP Publishing Ltd. Manipulation of the surface tension is useful in improving heat and mass transfer performances of nanofluids in thermal systems. In our previous study, the effect of microwave irradiation on the reduction of surface tension of nanofluids (Fe 2 O 3 ) was found even after it was turned off. In this study, a synergistic effect of microwave irradiation and surfactant addition (SDS) was investigated to obtain further surface tension reduction of nanofluid. Experimental results indicate that surfactant addition is effective for wider particle number density in reducing surface tension, and the reduction level strongly depends on the surfactant concentration. On the other hand, effect of the number density on the surface tension reduction is less significant for the same concentration of surfactant. From the obtained data, a combination of microwave irradiation and surfactant addition shows potential to be used as a promising method to manipulate surface tension of nanofluids.